A Zinc Cluster Transcription Factor Contributes to the Intrinsic Fluconazole Resistance of Candida auris - Eva-Maria Mayr; Bernardo Ramírez-Zavala; Ines Krüger; Joachim Morschhäuser (mSphere, 2020)
ABSTRACT The recently emerged pathogenic yeast Candida auris is a major concern for human health, because it is easily transmissible, difficult to eradicate from hospitals, and highly drug resistant. Most C. auris isolates are resistant to the widely used antifungal drug fluconazole due to mutations in the target enzyme Erg11 and high activity of efflux pumps, such as Cdr1. In the well-studied, distantly related yeast Candida albicans, overexpression of drug efflux pumps also is a major mechanism of acquired fluconazole resistance and caused by gain-of-function mutations in the zinc cluster transcription factors Mrr1 and Tac1. In this study, we investigated a possible involvement of related transcription factors in efflux pump expression and fluconazole resistance of C. auris. The C. auris genome contains three genes encoding Mrr1 homologs and two genes encoding Tac1 homologs, and we generated deletion mutants lacking these genes in two fluconazole-resistant strains from clade III and clade IV. Deletion of TAC1b decreased the resistance to fluconazole and voriconazole in both strain backgrounds, demonstrating that the encoded transcription factor contributes to azole resistance in C. auris strains from different clades. CDR1 expression was not or only minimally affected in the mutants, indicating that Tac1b can confer increased azole resistance by a CDR1-independent mechanism. IMPORTANCE Candida auris is a recently emerged pathogenic yeast that within a few years after its initial description has spread all over the globe. C. auris is a major concern for human health, because it can cause life-threatening systemic infections, is easily transmissible, and is difficult to eradicate from hospital environments. Furthermore, C. auris is highly drug resistant, especially against the widely used antifungal drug fluconazole. Mutations in the drug target and high activity of efflux pumps are associated with azole resistance, but it is not known how drug resistance genes are regulated in C. auris. We have investigated the potential role of several candidate transcriptional regulators in the intrinsic fluconazole resistance of C. auris and identified a transcription factor that contributes to the high resistance to fluconazole and voriconazole of two C. auris strains from different genetic clades, thereby providing insight into the molecular basis of drug resistance of this medically important yeast.